Tingkat Kesesuaian Konfigurasi Lanskap Berdasarkan Faktor Kepuasan Konfigurasi Area Aktivitas Primer - Muhammad Widad Bayuadi; Budi Sudarwanto; Edward Endrianto Pandelaki (Universitas Sebelas Maret Surakarta, 2022)
This study aims to obtain the formulation of research results related to the grade of satisfaction and the dominant satisfaction variable in the primary activity area of Nganjuk City Park. Qualitative descriptive research was used in this study, then the data was processed by qualitative data methods and processed using an Importance Performance Analysis (IPA) diagram which is then described using multiple linear regression analysis. The population survey used is city park users with a sample of 100 users. The sampling technique uses a sampling method based on certain characteristics (purposive sampling). In the results of the Importance Performance Analysis, it can be seen that in quadrants I to 4, there are priorities that must be hastened by changes or maintains configuration aspects so that the value of the satisfaction level of the configuration area can be maximized. Sequentially the priority changes that can be made are from the sports activity area (very dissatisfied) with the x;y quadrant points (9.68; 8.92); tours and stopovers (not satisfied) with quadrant points x; y (8.55; 10.84) and (9.11; 9.92); the learning area category (satisfied) with the x;y quadrant point (5.68;8.36), and the trading area category (very satisfied) with the x;y quadrant point (7.34; 10.03).